2019
DOI: 10.1136/bjsports-2019-100567
|View full text |Cite
|
Sign up to set email alerts
|

Can even experienced orthopaedic surgeons predict who will benefit from surgery when patients present with degenerative meniscal tears? A survey of 194 orthopaedic surgeons who made 3880 predictions

Abstract: ObjectivesTo examine the ability of surgeons to predict the outcome of treatment for meniscal tears by arthroscopic partial meniscectomy (APM) and exercise therapy in middle-aged patients.Design and settingElectronic survey. Orthopaedic surgeon survey participants were presented 20 patient profiles. These profiles were derived from a randomised clinical trial comparing APM with exercise therapy in middle-aged patients with symptomatic non-obstructive meniscal tears. From each treatment group (APM and exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
1
23
1
2
Order By: Relevance
“…Orthopedic surgeons received baseline characteristics of the patient including demographic information about employment, age and BMI, PROMs on pain, knee function and mechanical dysfunction, and MRI results on tear type and location, and radiograph information on level of knee osteoarthritis. Similar to the results of this study, they found that orthopedic surgeons were also unable to accurately predict which patient would benefit from physical therapy based on the baseline characteristics [20]. Positive beta is indicative that a higher score results in a higher probability of undergoing a meniscal surgery; a negative coefficient indicates that this risk increased with lower score.…”
Section: Discussionsupporting
confidence: 75%
“…Orthopedic surgeons received baseline characteristics of the patient including demographic information about employment, age and BMI, PROMs on pain, knee function and mechanical dysfunction, and MRI results on tear type and location, and radiograph information on level of knee osteoarthritis. Similar to the results of this study, they found that orthopedic surgeons were also unable to accurately predict which patient would benefit from physical therapy based on the baseline characteristics [20]. Positive beta is indicative that a higher score results in a higher probability of undergoing a meniscal surgery; a negative coefficient indicates that this risk increased with lower score.…”
Section: Discussionsupporting
confidence: 75%
“…Identifying patients with degenerative meniscal tears who have poor prognosis remains an unsolved puzzle, and research focusing on finding variables that influence treatment outcome is needed. 38 Our data provide evidence of specific prognostic factors for function in sport and recreational activities.…”
mentioning
confidence: 64%
“…However, this is comparable with other studies that have had similar outcomes (11% to 17% response rate) when surveying orthopaedic surgeons. 10 , 31 This low response rate creates a risk of selection bias. In the first survey, 53% of respondents routinely repaired the PQ muscle, while in the second this was reduced to 43%.…”
Section: Discussionmentioning
confidence: 99%